Double resonance capture of a two-degree-of-freedom oscillator coupled to a non-ideal motor - Gonçalves, P. J.P. [UNESP]; Silveira, M. [UNESP]; Petrocino, E. A. [UNESP]; Balthazar, J. M. [UNESP] (Springer Nature, 2016)
This work presents the development of a discrete parameter model consisting of a concentrated mass which is supported by a set of springs and dampers positioned in two orthogonal directions, such that the mass can move horizontally and vertically in a plane. A non-ideal motor is attached to the mass such that the phenomenon of resonance capture can occur. Resonance capture occurs in structures with low damping which are attached to rotating machines with limited power supply. When resonance capture occurs, the mean angular velocity of the motor remains constant and the displacement of the structure increases. An investigation on the influence of the two orthogonal resonance frequencies is presented. It was found that this model can illustrate the dynamics of a more complex structure consisting of a portal frame coupled to a non-ideal unbalanced motor. Experimental tests are used to support numerical simulations and the analytical model.
Keywords: Non-ideal motor; Resonance capture; Sommerfeld effect